Design of Web-Based Home Service Application Information System on The Sale and Repair of Motor Vehicle Spare Parts Workshop - Rudi Sutomo; Monica Vabiola Yanli (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
The sale and repair of motor vehicle spare parts workshopis small and medium business engaged in the sale and repair of motor vehicle spare parts which was established in 2000. Sales are made offline by opening a shop. CV Lancar Motor’s business makes sales by serving buyers who come by explaining the problems experienced by their vehicles then CV Lancar Motor’s experts will fix them.During the internship as Web Development at The sale and repair of motor vehicle spare parts workshopfor 60 woking days, the task given was to create a home service website to serve buyers form home, by bringing mechanics to the customer’s house. Making is done by making briefings and project integration and then followed by testing the website that has been made.The internship process that has been completed at The sale and repair of motor vehicle spare parts workshopprovides many benefits. Like getting experience how to be a Web Development that makes a website., it is hoped that it will provide useful knowledge and become a new experience in order to be able to do a better job in the real world of work.